MEMBANGUN COMPETITIVE ADVANTAGE SEKOLAH DALAM MENGHADAPI TANTANGAN GLOBALISASI - Asrulla Asrulla; Mukhtar; Kasful Anwar; Mahmud MY (LPPM Universitas Cipta Mandiri, 2024)
This paper discusses in depth about the competitive advantage of schools in facing the rapid competition among schools today. Competitive advantage serves the function of helping individuals have a very high capacity so that they understand the opportunities that come with globalization and the global economy, which can be utilized for the welfare of the nation and the development of the country. The objective conditions of the nation, global challenges, and information technology challenges make schools in Indonesia face very heavy pressure to build the best educational services, especially in the current era of digitization. Schools are confronted with the dynamics of the external environment. The external environment of these schools is a strategic environment where competencies are persistent and unstoppable. Therefore, a new conception of school excellence is needed to achieve service excellence to maintain the value of helping students in their participation in education. Thus, schools must be present in balance with good quality to have a competitive advantage. Openness to interact with various strategic supports is a very important characteristic and a tool to move faster, and also a tool to develop competitive advantage.